Over-admiring Celebrity in the Perspective of Islam - Sinta Rowina (Universitas Muhammadiyah Malang, 2024)
Over-admiring public characters, which often happens there is a lack of action or deeds because they are still adults who have not been adult, other effects in the real world usually someone who has been obsessed will vary a couple like the idol, to be the high criteria or the standard of the couple who should be exactly the idol. On the other hand, there is a waste if it meets or follows the idol style, or buy all the products in advertising or more known by the endorse by the artist. Phenomena of young people today, we can see the Mudayang boy imitating his idol style, the lands of even exit of Islamic Sharia. This is what the writer is interested in reviewing in depth initiative to live as much information to know what law is in the perspective of Islam, in terms of mental health, what if someone likes his opposite sexes, what is the advantage they get, we will learn from many sources, this is very interesting considering the idolizing a person or a grub again rally among the people especially young people.